2021
DOI: 10.1002/mp.15202
|View full text |Cite
|
Sign up to set email alerts
|

Toward magnetic resonance fingerprinting for low‐field MR‐guided radiation therapy

Abstract: Purpose The acquisition of multiparametric quantitative magnetic resonance imaging (qMRI) is becoming increasingly important for functional characterization of cancer prior to‐ and throughout the course of radiation therapy. The feasibility of a qMRI method known as magnetic resonance fingerprinting (MRF) for rapid T1 and T2 mapping was assessed on a low‐field MR‐linac system. Methods A three‐dimensional MRF sequence was implemented on a 0.35T MR‐guided radiotherapy system. MRF‐derived measurements of T1 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Previous works showed the feasibility of quantitative MRI on 0.35 T [31] , [32] and 1.5 T [26] , [33] , but not in the context of cardiac imaging. These studies demonstrated good agreement between their proposed qMRI methods and either gold-standard measurements or reference values on phantom.…”
Section: Discussionmentioning
confidence: 98%
“…Previous works showed the feasibility of quantitative MRI on 0.35 T [31] , [32] and 1.5 T [26] , [33] , but not in the context of cardiac imaging. These studies demonstrated good agreement between their proposed qMRI methods and either gold-standard measurements or reference values on phantom.…”
Section: Discussionmentioning
confidence: 98%
“…28 The dimensionality of the temporal subspace was experimentally set to K = 5. The R = 1 data sets were reconstructed using 20 iterations of a linear conjugate gradient algorithm (ie, without regularization), as this was previously demonstrated to agree well with ground-truth spin-echo measurements at 0.35 T. 14 The R = 2 reconstructions were performed using eight alternating direction method of multipliers iterations, five conjugate gradient iterations, LLR patch sizes of 8 × 8 pixels, and 𝜆 = 1 × 10 −4 . These parameters were all chosen experimentally.…”
Section: Reconstruction Implementationmentioning
confidence: 99%
“…An adiabatic inversion-prepared fast imaging with steady-state precession MRF sequence was implemented with stack-of-stars k-space coverage and a 512-point flip-angle pattern shown in our previous work. 14 Coronal stack-of-stars MRF data were acquired in the National Institute of Standards and Technology/International Society for Magnetic Resonance in Medicine system phantom 23 using a 12-channel torso coil array with a matrix size of 128 × 128 × 32 and spatial resolution of 1.64 × 1.64 × 5 mm. To match in vivo data, slice oversampling of 25% was used, bringing the total number of slice phase-encoding partitions to 40.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pilot study, a deep learning-aided MRF acquisition and reconstruction framework reduced the acquisition time from 21 minutes to a clinically feasible time frame. 98 Thorough evaluations of MRF sequence design with a 0.35 T ViewRay system, which could include optimization of FA/TR combinations and optimization of feasible acquisition time against acceptable accuracy and precision of MRF T 1 /T 2 maps, will warrant future studies.…”
Section: Potential Clinical Applications Of Mrf In Rtmentioning
confidence: 99%